(untitled) (Praxis Educativa, 2021)
This article describes the meanings teaching work acquires in precarious contexts. The meanings are taken from the point of view of a group of students of a teacher training program in San Martín. The hypothesis is that within social conditions of uncertainty for the teaching work, this activitty becomes an option to challenge conservative discourses and practices which deepen social and educational inequalities. The study is developed through an exploratory qualitative methodological approach. It uses in-depth interviews carried out since 2018 to the present. The interviews were made to first- and fourth-year students of the training course. Some of the results indicate that students desire regarding teaching are produced to respond to the need of doing something for the place they inhabit. That includes the desire of social change, to get some kind of social recognition, and to be able to transmit knowledge which may allow school students to be happy or to forget for a few moments the daily sadness.